Pandemic Events Caused by Bacteria Throughout Human History and the Risks of Antimicrobial Resistance Today - Pedro Filho Noronha Souza; Nicholas Silva dos Santos Filho; João Lucas Timbó Mororó; Daiane Maria da Silva Brito; Ana Beatriz da Lima; Felipe Pantoja Mesquita; Raquel Carvalho Montenegro (Microorganisms)
During human history, many pandemic events have threatened and taken many human lives over the years. The deadliest outbreaks were caused by bacteria such as Yersinia pestis. Nowadays, antimicrobial resistance (AMR) in bacteria is a huge problem for the public worldwide, threatening and taking many lives each year. The present work aimed to gather current evidence published in scientific literature that addresses AMR risks. A literature review was conducted using the following descriptors: antimicrobial resistance, AMR, bacteria, and Boolean operators. The results showed that antimicrobial-resistant genes and antibiotic-resistant bacteria in organisms cause critical infectious diseases and are responsible for the infections caused by antibiotic-resistant bacteria (ARB). This review emphasizes the importance of this topic. It sheds light on the risk of reemerging infections and their relationship with AMR. In addition, it discusses the mechanisms and actions of antibiotics and the mechanisms behind the development of resistance by bacteria, focusing on demonstrating the importance of the search for new drugs, for which research involving peptides is fundamental.